Investigation of the Relationship between University Students’ Health Belief Model Levels Regarding Sports Recreational Activities and Leisure Attitudes - Gül Yağar, Abdulkerim Çeviker, Çisem Ünlü (Pakistan Journal of Medical & Health Sciences, 2022)
Concerns of today’s health-related individuals have increased, especially in the last three years. With the changes in the field of education, it is aimed to examine the relationship between university students’ health beliefs and attitudes. The population of the research consisted of students between the ages of 18-25 studying at the Faculty of Sport Sciences of Hitit University, and the sample was 461 students. Ertüzün et al. (2013) "Health Belief Model Scale Regarding Sportive Recreation Activities" and "Leisure Time Attitude Scale" which was validated and reliable by Akgül and Gürbüz (2011). In the research findings, the most effective factor on leisure attitudes, which is defined as the U1 canonical variable, was determined as affective sub-dimension, and the most effective factor in the V1 canonical variable, which was defined as the health belief variable, was determined as perceived seriousness and psychosocial sub-dimension. When the canonical correlation values ​​are examined, the correlation value of U1 variable set and V1 variable set was .71, and the correlation value for U2 variable set and V2 variable set was .34, and it was concluded that the relationship was statistically significant. As a result, it has been determined that university students’ leisure attitudes affect their beliefs about their health.